THE IMPLEMENTATION ANALYSIS OF THE INCLUSION OF HEALTH WARNINGS AND HEALTH INFORMATION POLICY ON CIGARETTE PACKAGING - Ekawati, Diah; Darmawan, Ede Surya (UI Scholars Hub, 2019)
Pictorial health warnings already implemented for more than two years since June 24, 2014, however, there are no changes made following the Minister of Health Regulation No. 28 of 2013 until now. According to the results of the National Survey of Assessment of the Implementation of Pictorial Health Warning (PHW) in Indonesia in 2015 towards the compliance of the tobacco industry, it is known that the cigarette industry has not yet adhered to pictorial health warnings. The Government hopesthat the existence of the Minister of Health Regulation No. 28 can reduce the prevalence of smokers, but data from 2016 SIRKERNAS shows that the prevalence of smoking is increasing. The purpose is to dig deeper towards the implementation of the inclusion of health warnings and health information policy on cigarette packaging, henceforth it can be input into the formulation of tobacco control strategies. This study uses descriptive studies with qualitative analysis through in-depth interviews and document review. Aspects of the process (communication, bureaucratic structure and disposition), aspects of the actor (commitments and relationships) aspects of the content (level, benefits and policy objectives) as well as aspects of the context (political culture and socio-economic) are interrelated and influence each other in the implementation of the inclusion of warnings and health information on the cigarette packs. The implementation of the inclusion of warnings and health information on cigarette packaging has been carried out, and the level of industry compliance in including the PHW at the retail level has reached 99.91%. However, the cigarette industry is not compliant in fulfilling the provisions because the size is not appropriate, PHW images covered by excise tapes, and some terms indicate quality, superiority, security, and imaging.